If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2.1y+3.6=1.1+0.6y
We move all terms to the left:
2.1y+3.6-(1.1+0.6y)=0
We add all the numbers together, and all the variables
2.1y-(0.6y+1.1)+3.6=0
We get rid of parentheses
2.1y-0.6y-1.1+3.6=0
We add all the numbers together, and all the variables
1.5y+2.5=0
We move all terms containing y to the left, all other terms to the right
1.5y=-2.5
y=-2.5/1.5
y=-1+1/1.5
| 7x-14=42* | | 4xx2=78 | | 4(3x+6)=8(1.5x+3) | | 7c+5=9 | | -13f=-11-14f | | 2x-(14)=-3+6 | | 3y+7-2y=8 | | v-20=80 | | z-50=2 | | 180-2x+6x=90 | | -3.1p+2.5=18 | | 5p+17-9p=-15+4p | | 115+m=180 | | 3/4x+37=2/5x-68 | | x2+200x=166,400. | | x^2+3x=-1x+5 | | -1+2k=3 | | 6a+3=69 | | y–21=18 | | 1.50(c+5)-10=-4 | | 56+1.5x=180 | | 17x+5=7x+25 | | 7n+8=11n | | 6=d3 | | 3=y+86 | | 25=-4x-2x+-5 | | 56+1/2x=180 | | 6k+5=2k+1,k= | | 6a+3=69* | | 2x+x+(x+10)=70 | | 2m2+2m2=144 | | x-6.3=-5.2 |